Implementation of IR 4.0 and IIoT in various research and TnL activities at IIUM - Saleh, Tanveer; Abdulrahman, Dakhel; Banawair, Mohammed; Irfan Fikhri bin, Iszahar (2023)
This talk broadly covered our (IIUM's) T&L and research activities related to the three aspects of IR 4.0